Goldilocks at work: Just the right amount of job demands may be needed for your sleep health - Nelson, Monica E; Lee, Soomi; Allen, Tammy D; Buxton, Orfeu M; Almeida, David M; Andel, Ross (Sleep health, 2023)
OBJECTIVES: It has been reported that job demands affect sleep, but how different levels of job demands affect sleep remains unclear. We examined whether curvilinear relationships exist between job demands and multiple sleep health outcomes. DESIGN: Cross-sectional analyses with linear and quadratic effects, using self-administered survey data. SETTING: A national sample of US adults. PARTICIPANTS: Workers from Midlife in the United States Study (MIDUS2; n = 2927). MEASUREMENTS: The Job Content Questionnaire assessed overall and 5 specific aspects of job demands (intensity, role conflict, work overload, time pressure, and interruptions). Habitual sleep health patterns across 5 dimensions (regularity, satisfaction/quality, daytime alertness, efficiency, and duration) were assessed. Age, sex, race/ethnicity, marital/partnered status, education, job tenure, work hours, body mass index, smoking status, and study sample were covariates. RESULTS: There were significant linear and quadratic relationships between job demands and sleep outcomes. Specifically, the linear effects indicated that participants with higher job demands had worse sleep health, such as shorter duration, greater irregularity, greater inefficiency, and more sleep dissatisfaction. The quadratic effects, however, indicated that sleep regularity and efficiency outcomes were the best when participants' job demands were moderate rather than too low or too high. These effects were found for overall job demands as well as for specific aspects of job demands. Stratified analyses further revealed that these curvilinear associations were mainly driven by participants with low job control. CONCLUSIONS: Moderate levels of job demands, especially if combined with adequate job control, are related to optimal sleep health.
Keywords: Smoking; průřezové studie; psychický stres; Cross-Sectional Studies; Sleep; Adult; Spojené státy americké; lidé; dospělí; Surveys and Questionnaires; United States; Humans; kouření; Stress, Psychological; průzkumy a dotazníky; spánek